Setting Priorities, Building Prosperity through Universal Health Coverage - Evans, Timothy G.; Palu, Toomas (Taylor and Francis, 2016)
Since 2000, a growing number of governments around the world have made the political commitment to undertake reforms toward Universal Health Coverage (UHC). According to our analysis, UHC efforts in 24 frontrunner countries have been massive and transformational. And with the recent adoption of UHC as a target in the Global Goals for 2030, policy makers are more than ever making it a priority to ensure that all their citizens have access to quality, essential health services and that no one falls into or remains in poverty because of paying for the care they need.